Penerapan Metode Takrir dalam Meningkatkan Hafalan Surah Pendek Santri di TPA Miftahul Jannah Kota Kapur - Rudini Rudini (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
The Quran is the main guide for Muslims. Studying and reading it is worth worship. Therefore, to maintain and maintain the authenticity of the verses of the Quran, Muslims do memorization. One of the processes of memorizing the verses of the Quran is carried out at the TPA education level, especially the Miftahul Jannah TPA, Kota Kapur. However, the problem found in the process of memorizing short suras at TPA Miftahul Jannah is that there are students who have difficulty memorizing. Therefore, the tikrar method is applied in the memorization process. The research method in examining the application of the takrir method in improving the memorization of short surahs at the Miftahul Jannah TPA is using a qualitative method. Data collection techniques using interviews, observation, and documentation. The results of this study indicate that the application of Takrir method at Miftahul Jannah TPA Kota Kapur with the following steps: a) Determine the letter, b) The teacher gives examples of reading or demonstrates the reading, c) Reads together and repeatedly. d) Provide the right simulation, deposit memorization, e) Evaluation and f) Game.